Obsession and Maladaptive Search for Raison D’être: A Condition That May Harm Psychological Wellbeing - Akaishi, Tetsuya (Frontiers in Psychology, 2022)
Being with raison d'être, or the meaning of living, usually has a positive effect on the psychological well-being of humans. The impact of an endeavor or desire to be with raison d'être on human well-being remains undetermined. This study investigated the potential impact of an obsession with raison d'être on human psychological well-being. A literature review revealed that only a limited number of studies have evaluated the relationship between attitudes toward raison d'être and psychological well-being. Some indicate that a pathological obsession with a self-oriented raison d'être, especially when the search is attempted via maladaptive ways, may eventually cause harm and distress to those who are the object of obsession and the surrounding people. If obsessed people persist to preserve raison d'être in the community, they need to continuously demonstrate the advantage of their existence and differentiation from other members. As conceivable adaptive ways to search for raison d'être, people make efforts to enhance their talents, achieve certifications, be promoted, or dedicate themselves to volunteers. However, if these adaptive ways have failed, some obsessed people may change their processes to maladaptive ways, such as attacking or criticizing other members who are a threat to their satisfaction with raison d'être. Such maladaptive approaches in the community would harm both the obsessed and surrounding members. To date, the negative aspect of desiring for raison d'être remains largely unevaluated. Research regarding the prevalence of pathologic obsession with raison d'être in the general population, its impact on human well-being, and treatability are warranted.